Hukum dan Hak Asasi Manusia di Indonesia - Annisa Rembang Mustika (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2023)
Protection related to human rights (Human Rights) is one of the principles that must be owned by the Indonesian state. Constitutional protection of human rights with legal guarantees for demands for enforcement through a fair process. A true rule of law is a country that upholds justice in the legal process such as the occurrence of human rights violations. The purpose of this research is to examine human rights violations in Indonesia and their enforcement. The research method used is a qualitative method. This research is library research so the sources come from books, scientific articles, and other relevant sources. The results of the research show that human rights are rights that are indeed owned by all people. However, there are still violations of human rights law. The punishments received by human rights violations have not fully had a deterrent effect. Therefore, law and human rights in Indonesia must coexist to uphold the fairest law against perpetrators of human rights violations.